Peluang dan Tantangan: Menyambut Kembali ke Indonesia: Opportunity and Challenge: Welcoming Back to Indonesia - Riyanti, Yulia Eka; Murwaningsari, Etty; Gunawan, Juniati; Aryati, Titik; Siagian, Yolanda Masnita; Yusran, Husna Leila; Nurhayati, Nimati Andini (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This activity is part of a Community Service Program (PKM) conducted by the Doctoral Program in Economics (PDIE), with a concentration in Accounting, at the Faculty of Economics and Business, Trisakti University, in collaboration with students currently pursuing their education at Wageningen University and Research (WUR). The program aims to exchange information on the topic: "Opportunity and Challenge: Welcoming Back to Indonesia." The PKM activity took place on May 2, 2025. The method used was a sharing session with students currently studying at WUR. The PKM activity was attended by 15 WUR students, comprising undergraduate, master's, and doctoral (PhD) students, as well as 20 PDIE participants, including lecturers, students, and alums. The outcome of this PKM was that participants gained insights into the differences in educational approaches between WUR and universities in Indonesia, particularly Trisakti University. At WUR, the learning process is research-based and not tied to a specific study program from the outset, which contrasts with Indonesia, where students choose their major at the beginning of their studies. The PKM activities conducted by the lecturers not only provided benefits to the participants through shared experiences but also led all attendees to understand that today's education system is more integrated, less compartmentalized, and ideally should focus on problem-solving, involving research with an implementation-oriented approach.